Criticality and English Language Education: An Autoethnographic Journey - Raúl Alberto Mora (Asociación Colombiana de Profesores de Ingles, 2021)
This article, relying on a series of epiphanies throughout my journey as a researcher and scholar-activist, shares my relationship with criticality and how it has guided my research and teaching agendas. I share how critical theories have informed my main research areas and the questions and issues I have raised in my own work. The article also discusses my main scholarly influences and how my interactions with varied literature, mentors, and colleagues have shaped my own criticality. I also take a moment to reflect on how this journey has helped the field of language education in Colombia to continue with the evolution toward stronger critical and social justice-oriented frameworks and how I see my changing positionality as mentor and ally of colleagues and the future cadres of scholars moving forward.